Association between gastroprotective agents and risk of incident interstitial lung disease in systemic sclerosis. (August 2021) - Hurtubise, Raphaël; Hudson, Marie; Gyger, Geneviève; Wang, Mianbo; Steele, Russell J.; Baron, Murray; Hoa, Sabrina
Abstract: Objectives: Although interstitial lung disease (ILD) occurs in over half of systemic sclerosis (SSc) patients and represents a leading cause of mortality, there are currently no preventative strategies. We evaluated if gastroprotective agents were associated with a lower incident risk of SSc-ILD. Methods: An SSc cohort without clinically apparent ILD at baseline was constructed from the Canadian Scleroderma Research Group registry. The primary exposure was any use of gastroprotective agents. Treatment with promotility agents was assessed as a secondary exposure. Time to development of clinically apparent ILD was compared between exposed and unexposed person-time, using a multivariable marginal structural Cox model incorporating inverse probability of treatment weights to address time-varying confounding. Results: In total, 798 subjects met inclusion criteria. At cohort entry, median disease duration was 7.6 (IQR 3.9–15.6) years. During a median 4.4 (IQR 2.6–7.2) years of follow-up, 158 new ILD cases were diagnosed, for a crude incidence of 4.4 (95% CI 3.8–5.1) events per 100 person-years. Most (2085, 73.4%) person-visits were exposed to gastroprotective agents, 579 (20.4%) were exposed to promotility agents, and 554 (19.5%) were exposed to both agents. The marginal structural weighted hazard ratio (HR) for incident ILD related to gastroprotective agents was 0.86 (95% CI 0.52–1.41). When exposure was defined as treatment with promotility agents, the weighted adjusted HR was 0.79 (95% CI: 0.35–1.77). Conclusion: In this large retrospective cohort study, we were unable to demonstrate a protective role for gastroprotective and promotility agents in preventing clinically apparent SSc-ILD. Highlights: We studied a large observational cohort of systemic sclerosis patients. Gastroprotective agents did not prevent incident scleroderma lung disease. Promotility agents did not prevent incident scleroderma lung disease.